2017
DOI: 10.1038/s41598-017-11053-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated mean platelet volume predicts poor prognosis in colorectal cancer

Abstract: Altered mean platelet volume (MPV) is implicated in several malignancies. However, the clinicopathological significance and prognostic value of MPV in colorectal cancer (CRC) is still elusive. The purpose of this study was to elucidate the predictive significance of MPV in CRC. The retrospective study recruited 509 consecutive CRC patients between January 2009 and December 2009. The relationships between MPV and clinicopathological characteristics were analyzed. Kaplan-Meier method and Cox regression were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 18 publications
2
56
0
Order By: Relevance
“…Many scholars have reported that MPV levels might serve as potential biomarkers for the diagnosis and early recognition of different stages of CRC . Furthermore, it was previously reported that patients with increased MPV had worse survival rates than those of patients with normal MPV levels . Additionally, one study found that the PDW levels of patients with CRC were higher than those in healthy participants but lower than those in adenomatous patients .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many scholars have reported that MPV levels might serve as potential biomarkers for the diagnosis and early recognition of different stages of CRC . Furthermore, it was previously reported that patients with increased MPV had worse survival rates than those of patients with normal MPV levels . Additionally, one study found that the PDW levels of patients with CRC were higher than those in healthy participants but lower than those in adenomatous patients .…”
Section: Discussionmentioning
confidence: 99%
“…As independent prognostic factors, MPV, PDW, and monocytes are easily collected from routine blood tests. It has been proposed that these factors might help stratify patients with cancer into those who may or may not benefit from adjuvant chemotherapy . One study showed that systemic chemotherapy and regional chemotherapy reduced hematogenous metastasis in patients with CRC after resection, suggesting improved survival rates .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is frequently characterised by a hypercoagulable state and a mean platelet volume can predict poor prognosis in some cancers [90,91]. Platelets are implicated in cancer progression and metastasis by preventing intra-tumoural haemorrhage, and promoting angiogenesis and the tethering and arrest of circulating tumour cells.…”
Section: Tumour Resident Cells That Mediate Immunosuppressionmentioning
confidence: 99%
“…4 This might make this laboratory test difficult to use in routine clinical work unless the pathophysiological basis for the effect of extremes in platelet size can be established. Important questions about this effect are: We initially searched the MEDLINE database using PubMed with the MeSH term mean platelet volume to determine if there were many clinical studies with this laboratory test.…”
Section: Clinical Questionsmentioning
confidence: 99%